A review of the families and genera of the superfamily PLATYSCELOIDEA Bowman & Gruner, 1973 (Crustacea: Amphipoda: Hyperiidea), together with keys to the families, genera and species - Zeidler, Wolfgang (Zootaxa, 2016)
The systematics and phylogenetic relationships of the families and genera of the superfamily Platysceloidea are examined, following a thorough examination of the morphology of an example of the type species of each genus, or a substitute species if the true identity of the type species is in doubt. The mouthparts are described for each type species, often for the first time, providing additional characters for phylogenetic analysis. Genera are diagnosed using the taxonomic database program DELTA (Dalwitz et al. 1999). This database is also used for a phylogenetic analysis of the genera using PAUP (Swofford 2000). Proposed taxonomic changes resulting from this study are summarised as follows. The family Pronoidae is restricted to the monotypic genus Pronoe because it has some unique characters not found in any other platysceloidean. Paralycaea, previously in Pronoidae, has characters in common with Amphithyrus and Amphithyropsis gen. nov., a new genus proposed for Paralycaea platycephala Zeidler, 1998 (here re-determined a junior synonym of Tetrathyrus pulchellus Barnard, 1930), and together they form the proposed new family Amphithyridae fam. nov. Eupronoe and Parapronoe, also previously in Pronoidae, are similar in the morphology of the mouthparts, antennae and gnathopoda, and together form the proposed new family Eupronoidae fam. nov. The family Brachyscelidae is restricted to the genus Brachyscelus because Thamneus, previously included in Brachyscelidae, has a number of characters that differ considerably from any other genus of Hyperiidea and it is therefore placed in a family of its own, Thamneidae fam. nov. The status of the family Anapronoidae, for Anapronoe, is confirmed, as is the status of the family Tryphanidae for Tryphana. The family Lycaeidae is limited to Lycaea and Simorhynchotus. The family Oxycephalidae maybe polyphyletic but more work is required to resolve the systematic status of the eight genera currently recognised. Metalycaea globosa Stephensen, 1925, sometimes included in the Oxycephalidae, is confirmed to be a junior synonym of Lycaea serrata Claus, 1879. The family Platyscelidae is restricted to four genera, Platyscelus, Paratyphis, Hemityphis and Tetrathyrus; Amphithyrus having been removed to the new family Amphithyridae. The family Parascelidae is also restricted to four genera, Parascelus, Thyropus, Schizoscelus and Euscelus. Hemiscelus, previously included in this family, is regarded a junior synonym of Hemityphis. Keys are provided for families, genera and all currently known species. All records of associations with gelatinous zooplankton are also documented, providing additional data to help resolve the phylogeny and evolutionary origins of the Hyperiidae.